A Review of Electromagnetic Safety Protection Technologies - Wen, Zheng; Leong, Wai Yie (INTI International University, 2025)
This paper provides a systematic review and comparative analysis of five pivotal electromagnetic-compatibility (EMC) and safety-protection technologies: the “OODA-loop”-based intelligent protection system, shielding techniques, energy-selective electromagnetic protection, cooperative electromagnetic-security suppression, and electromagnetic-noise jamming. By clarifying their technical principles, applicable scenarios, and current state-of-the-art, the study offers a reference for technology selection under diverse application requirements and for future research directions. A systematic review and analysis of the relevant technical literature and experimental reports was conducted, focusing on the working principles, typical applications, and measured performance of each technology. The results indicate that OODA-loop-based systems offer high automation and rapid response, making them well-suited for facility-wide protection of large-scale infrastructures; shielding techniques are the most mature and lowest-cost solution, hence the most widely deployed; energy-selective protection achieves nanosecond-level adaptive suppression, effectively countering high-power electromagnetic pulses entering through intended apertures, but at higher expense; cooperative suppression technology significantly improves jamming effectiveness and resource utilization through optimized algorithms; and electromagnetic-noise jamming, being mature and straightforward, is mainly employed for low-level information-leakage prevention. Each technology presents distinct advantages and limitations, necessitating judicious selection according to the specific operational scenario. This review compares their application contexts and highlights advantages/limitations.